Pengaruh Celebrity Endorser, Fanatisme Penggemar Dan Merchandise Terhadap Keputusan Pembelian Mie Lemonilo (Studi Kasus NCTzen Indonesia) - Sri Wahyuni, Erika; Zainarti; Atika (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2024)
This research discusses the influence of celebrity endorsers, fan fanaticism and NCT Dream fan merchandise on the purchase decision of Mie Lemonilo. The independent variables in this study were celebrity endorsers, fan fanaticism, and merchandise while the dependent variables were the decision to buy Mie Lemonilo. The research method used is a quantitative research method with a total of 100 respondents obtained using a nonprobability sampling method from the entire NCTzen population who are followers of @7dreamsbt Twitter account. This study uses IBM SPSS Statistic 27 software and the results of this study show that celebrity endorsers, fan fanaticism, and merchandise have a positive and significant effect on the purchase decision of Mie Lemonilo.